Effects of land use practices on the organic carbon content, cation exchange capacity and aggregate stability of soils in the catchment zones - Heshmati, Mosayeb; Abdu, Arifin; Jusop, Shamsuddin; Nik Ab. Majid, Nik Muhamad (Science Publications, 2011)
Problem statement: Land use practice leads to changes in the physico-chemical properties of soils, such as Soil Organic Carbon (SOC), Cation Exchange Capacity (CEC) and Soil Aggregate Stability (SAS) that cause soil erosion. Approach: Merek catchment, Iran suffers from land degradation due to poor land use practice. A study was carried out with the objectives: (i) to determine soil nutrient status in different agro-ecological zones in Merek catchment; and (ii) to evaluate the influence of land use practices on SOC, CEC and SAS. Results: It was found that soil texture was silty and clay, while soil reaction was alkaline (pH was 7.75). The respective amount of carbonates was 32 and 36% in the top-soil and sub-soil respectively, indicating high level of alkalinity in the soils of the study area. The mean SAS of the surface soil layer for agriculture, rangeland and forest was 53, 61 and 64%, respectively with its mean in the topsoil of agriculture is significantly lower (P≤0.05) than the other zones. SOC level in the agriculture, rangeland and forest were 1.35, 1.56, 2.14% in the topsoil and 1.03, 1.33 and 1.45%, in the subsoil of the respective areas. The results of t-test and ANOVA analyses showed that SOC means are significantly different from each other within soil depth and among agro-ecological zones. The CEC in the agriculture, rangeland and forest areas were 25.8, 24.6 and 35.1 cmol ckg -1 for the top-soil and 31.1, 26.8 and 26.9 cmol ckg -1 in the sub-soil, respectively. All the above changes are due to the negative effects of agricultural activities. Conclusion: Improper tillage practice (up-down the slope), conversion of the rangeland and forest to rain-fed areas, crop residue burning, over grazing and forest clearance contribute to reduction in SOC and SAS in the Merek catchment, Iran.